The Effect of Earnings Management, Managerial Ownership, and Firm Size on Environmental Disclosure with Environmental Performance as Moderating - Chaq, Vida Chusnia; Wahyudin, Agus (Accounting Analysis Journal, 2020)
The purpose of this study is to analyze and determine the effect of earnings management, managerial ownership, and firm size on environmental disclosure by environmental performance as moderation. Non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2014-2017 as many as 385 companies were taken as the population in this study. The use of purposive sampling method produced 64 units of analysis from 16 companies. Moderate regression analysis through absolute number differences was applied as a data analysis technique using the IBM SPSS 24 Program. The results of this study indicate that earnings management, managerial ownership, and firm size do not have significant effect on environmental disclosure. In addition, environmental performance does not significantly moderate the effect of earnings management on environmental disclosure and does not significantly moderate the effect of firm size on environmental disclosure. Environmental performance can only significantly moderate the effect of managerial ownership on environmental disclosure. This study concludes that only managerial ownership driven by environmental performance will affect the extent of the company’s environmental disclosure.